“Se imprima y circule”: management and control of the book into the Kingdom of Navarre (1801-1831) - Ruiz Astiz, Javier (Revista General de Información y Documentación, 2015)
This article aims to unravel the role of Royal Council of Navarre between 1801 and 1831 from the analysis of the 87 printing authorization dossiers preserved into the General Archive of Navarre. Thanks to them we are able to discern the administrative operation of the editing process in the kingdom in early nineteenth century, and the purpose of such requests (licenses, censures or reprints), who was behind them and what type books were enrolled.